K-685, a TRPV1 Antagonist, Blocks PKC-Sensitized TRPV1 Activation and Improves the Inflammatory Pain in a Rat Complete Freund's Adjuvant Model - Yoshiyuki Sugimoto; Yozo Kojima; Atsushi Inayoshi; Kazuaki Inoue; Hiroko Miura-Kusaka; Kiyotoshi Mori; Osamu Saku; Hiroshi Ishida; Eri Atsumi; Yoshisuke Nakasato; Shiro Shirakura; Shin-ichiro Toki; et al. (Elsevier, 2013)
Transient receptor potential vanilloid 1 (TRPV1) is a Ca2+-permeable non-selective cation channel that transmits pain signals. TRPV1 is activated by multiple stimuli such as capsaicin, acid, and heat. During inflammation, TRPV1 is reported to be sensitized by protein kinase C (PKC) in dorsal root ganglia (DRG) neurons, which leads to reduction in the threshold of the temperature for TRPV1 activation to body temperature. This sensitization is considered to contribute to chronic inflammatory pain. In a previous study, we discovered orally active 5,5-diarylpentadienamide TRPV1 antagonists. To examine the effects of our TRPV1 antagonists on PKC-sensitized TRPV1, we developed an in vitro assay system to monitor the TRPV1 sensitization by PKC. In this assay system, our TRPV1 antagonists, such as (2E,4Z)-N-[(3R)-3-hydroxy-2-oxo-1,2,3,4-tetrahydro-5-quinolyl]-5-(4-isopropoxyphenyl)-5-(4-trifluoromethylphenyl)-2,4-pentadienamide (K-685), inhibited the activation of TRPV1 sensitized by PKC. The potentiation of heat-induced inward currents by PKC was seen in rat DRG neurons, and K-685 attenuated these currents. Furthermore, K-685 reversed the thermal hyperalgesia and mechanical allodynia in a rat complete Freund's adjuvant-induced inflammatory pain model. These results therefore suggest that K-685 has a strong potential as a new analgesic drug for the treatment of inflammatory pain. Keywords:: TRPV1 antagonist, pain, protein kinase C (PKC), inflammation, complete Freund's adjuvant (CFA)